FRAMING ANALYSIS OF THE NEWS COVERAGE OF PRESIDENTIAL CANDIDATE 01 IN 2024: A COMPARATIVE STUDY OF KBANEWS AND TIRTO.ID: ANALISIS FRAMING PEMBERITAAN CAPRES 01 TAHUN 2024: STUDI PERBANDINGAN KBANEWS DAN TIRTO.ID. - Alam An Shori; Aldrian Aldrian; Mellinda Raswari Jambak; Nabila Nur Khonsa; Wildana Wargadinata (Jurnal Kata, 2024)
The national news media is very influential in changing people's views in determining the choice of presidential and vice presidential candidates for 2024.  The third presidential debate held at Istora Senayan Jakarta went well. This research aims to: (1) reveal Robert Entmant's framing analysis and framing devices in the news of presidential candidate 01 in 2024 on online news sites kbanews and tirto.id, (2) reveal the reasons behind the differences between kbanews and tirto.id in framing news about presidential candidate 01 in 2024. This type of research is qualitative, with primary data sources from  online news sites, kbanews and Tirto.id. The data collection techniques used are reading and recording. While the data analysis technique goes through 3 stages, namely reducing data, describing data, and drawing conclusions. The results of this study found two different forms of framing. The online news media site kbanews tends to side with presidential candidate number 01, as can be seen from the diction used in the third debate. The media is proud of Anies Baswedan who appeared convincing. Meanwhile, the online news media site tirto.id tends to criticize Anies Baswedan for talking about Indonesia's defense system. The reason for the difference in the news framing of the two media is that the KBA News news media basically produces news that focuses on positive things about Anies Baswedan, while tirto.id is media that tries to be neutral in reporting on existing issues.